Development of English Board Learning Media to Increase Learning Motivation in English Subjects in Grade 3 of Elementary Madrasah - Novitaningrum, Diah Tri; Alfiyah, Hanik Yuni; Sa’diyah, Siti Halimatus (Tarsib: Jurnal Program Studi PGMI, 2024)
Students are less motivated to follow the English learning process. The methods and approaches used by teachers are less interesting to students, still centered on the teacher. This study developed English board learning media, and to increase student enthusiasm and make it easier for teachers to transfer knowledge to students. English Board is expected to be fun, interesting, and motivating, and not make students bored when participating in English learning activities. The "English Board" learning media can increase student enthusiasm in learning and provide a pleasant learning experience for students. English Board media uses a research and development model. This study was only conducted in five stages, namely: 1) potential and problem stage, 2) data collection stage, 3) product design stage, 4) product validation stage, and 5) product revision stage. The results of the media validity obtained an average percentage of 89.77%, this result is included in the category of very good or very suitable for use in implementing English learning activities.